Food overlap between Vimba vimba (L., 1758) and Scardinius erythrophthalmus (L., 1758) in Büyükçekmece Reservoir (Turkey) - Gülşah Saç (Turkish Journal of Bioscience and Collections)
The feeding habits of two omnivorous fish species, Vimba vimba (L., 1758) and Scardinius erythrophthalmus (L., 1758) from the Büyükçekmece Reservoir (Turkey) were investigated through stomach content analyses. Samplings were carried out monthly to describe the dietary composition of two species and to assess whether it overlapped. The diet spectrum of V. vimba consisted of eight prey categories: Diptera, Insecta extremities, plants, Cladocera, Bivalvia, Ostracoda, Pisces and detritus. Detritus has the highest value in terms of modified index of relative importance and it was followed by Insecta. The diet composition of S. erythrophthalmus consisted of four prey categories: Insecta extremities, plants, Bivalvia and detritus. Plant has the highest value in terms of modified index of relative importance and it was followed by detritus. No dietary overlap was detected, except for the fish collected in spring. Fractional trophic level (TROPH) and its standard error (SE) were estimated as 2.62±0.25 for V. vimba and 2.45±0.19 for S. erythrophthalmus.